2002
DOI: 10.1364/ol.27.000107
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous NO and CO_2 measurement in human breath with a single IV–VI mid-infrared laser

Abstract: A tunable diode laser absorption spectroscopy (TDLAS) system equipped with a IV-VI mid-IR laser operating near 5.2>mu;m was used to measure exhaled nitric oxide (eNO) and carbon dioxide (CO(2)) simultaneously in human breath over a single exhalation. Breath was sampled in real time, and eNO levels were measured from seven volunteers, two steroid-naive asthmatics and five nonasthmatics. Measured CO(2) levels were used as an internal standard to verify correct breath collection and calculate eNO values. Calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 12 publications
0
23
0
1
Order By: Relevance
“…Optical Absorption Spectroscopy (OAS) has been used to assess oxidative stress for a range of clinical applications including a wavelength-modulation system that measures ethane in breath [90], and a mid-infrared (IR) high-resolution Tunable Laser Absorption Spectroscopy (TLAS) system to measure exhaled nitric acid and carbon dioxide in human breath [91,92]. Baum et al [93] reported use of Ultraviolet Absorption Spectroscopy (UVAS) to measure acetylene in breath for monitoring cardiac output.…”
Section: History Of Aroma and Electronic Noses In Biomedicinementioning
confidence: 99%
“…Optical Absorption Spectroscopy (OAS) has been used to assess oxidative stress for a range of clinical applications including a wavelength-modulation system that measures ethane in breath [90], and a mid-infrared (IR) high-resolution Tunable Laser Absorption Spectroscopy (TLAS) system to measure exhaled nitric acid and carbon dioxide in human breath [91,92]. Baum et al [93] reported use of Ultraviolet Absorption Spectroscopy (UVAS) to measure acetylene in breath for monitoring cardiac output.…”
Section: History Of Aroma and Electronic Noses In Biomedicinementioning
confidence: 99%
“…Mass spectrometry techniques include gas chromatographymass spectrometry (GC-MS), 11,14 proton transfer reactionmass spectrometry (PTR-MS), 15,16 and selected ion flow tube-mass spectrometry (SIFT-MS). 17,18 Optical spectrometry techniques include cavity ring down spectroscopy (CRDS), 19,20 tunable diode laser absorption spectroscopy (TDLAS), 21 and photoacoustic spectroscopy (PAS). 22 Similar collection, purification/concentration, and analyses stages are used with these technologies and accuracies in the parts per billion by volume (ppbv) range are achievable.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a number of efforts have focused on the application of MIR spectroscopy and sensing schemes to human EB analysis for the identification of diseases [26,38,39]. The group of Mizaikoff [21] has constructed MIR broadband gas sensing systems based on FT-IR spectrometers, a 1 m long hollow-core waveguide gas cell, and a mercury-cadmium-telluride (MCT) detector, thereby successfully demonstrating simultaneous multianalyte sensing with detection sensitivities of 15.8 ppb for CO 2 and 517 ppb for CH 4 .…”
Section: Mid-infrared Optical Sensorsmentioning
confidence: 99%
“…Roller et al [38] have constructed a tunable diode laser absorption spectroscopy (TDLAS) sensing system utilizing IV-VI narrow bandgap MIR diode lasers with an emission wavelength of 5.2 μm combined with a 107 m long multipass White cell to quantitatively detect NO and CO 2 in human breath for the diagnosis of asthmatic conditions in EB, as shown in Figure 46 QCLs, the conduction band structure of active regions and injection regions (digitally graded alloy) is schematically shown. The digitally graded alloy region also consists of several quantum wells (superlattice) with the fine structure omitted for simplicity in this diagram.…”
Section: Mid-infrared Optical Sensorsmentioning
confidence: 99%
See 1 more Smart Citation